EFFECT OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE TO USAGE DECISION GRAB ONLINE TRANSPORTATION SERVICE IN SIDOARJO REGENCY AREA - Yosediputra, Afandy; Supriyono, Supriyono (Yayasan Education and Social Center, 2024)
The rapid advancement of information technology has significantly impacted various aspects of human life. One notable innovation stemming from these technological developments is the online transportation industry. This sector has experienced substantial growth, with the emergence of online transportation booking applications intensifying market competition in recent years. One of the most widely used online transportation service applications in Indonesia is Grab. However, the Grab index value has seen a consistent decline over the past four years. Based on this, the research aims to examine the impact of perceived usefulness and perceived ease of use on the decision to use Grab's online transportation services. The study utilizes primary data collected from respondents residing in the Sidoarjo district. Data analysis is conducted using the partial least squares technique. The findings of the study indicate that perceived usefulness positively influences usage decisions, with a path coefficient of 0.352800 and a T-statistic of 4.247931, which is greater than the critical Z value at α = 0.05 (5%) = 1.96, making the influence statistically significant. Additionally, perceived ease of use also positively impacts usage decisions, with a path coefficient of 0.518550 and a T-statistic of 6.812777, also exceeding the critical Z value, confirming a statistically significant positive influence